Develop a programme to predict seismic base shear force of type 2 elastic response spectra according to EUROCODE 8 - Chow Jia Yi (School of Environmental Engineering, University Malaysia Perlis, 2013)
The main objective of this project is to develop a user friendly programme where seismic lateral force as known as base shear force can be computed efficiently.